Effects of water stress on rice production: bioavailability of potassium in soil - Jahan, Md Sarwar; Nordin, Mohd Nozulaidi; Che Lah, Mohd Khairi; Yusop, Mohd Khanif (Vikol Publishing, 2013)
Water demand in agriculture, municipal, and industrial purposes is increasing rapidly which will pressure on future demand in agriculture. To justify less water use in rice production, we produced rice under different water levels (DWLs) and justified potassium bioavailability. There were five DWLs were employed in this experiment. Besides measuring yield and yield parameters, relative water content (WRC) and chlorophyll content in leaves, soil pH and bioavailability of potassium (K) in soil solution were measured. Yield and yield parameters showed insignificant difference under DWLs. Different water levels did not affect weekly data of chlorophyll content and RWC in leaves. But chlorophyll content and RWC in leaves were significantly higher in week 6 or 9 than week 3. Different water levels did not affect soil pH. Our results suggested that rice can be produced under low water input without affecting yield and yield parameters and K bioavailability in soil.